Analysis Of Consumer Behavior Related To The Increase In Rice After The 2024 Election In Surakarta City - Musthofa Wahyu Utomo, Mohammad Ali; Setiyani, Rahmawati; Rahyunanto, Setyo (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze consumer behavior related to the increase in rice prices after the 2024 election in Surakarta City. The increase in rice prices is often an important issue in the context of the household economy, especially for consumers in urban areas such as Surakarta. Data of this study was obtained by a survey method that includes a quantitative approach from a sample of households in various sub-districts in Surakarta City. Through the analysis of the data obtained, this study explores the impact of rising rice prices on consumption patterns, changes in household budgets, and adaptation strategies implemented by consumers. The study's conclusions demonstrate that consumer spending patterns are not considerably impacted by the rise in rice prices following the election. In addition, the economic impact of the increase in rice prices also causes changes in household budget allocations, where consumers tend to prioritize spending on other basic needs. This study provides insight into how changes in food prices affect the economic well-being of households and provides recommendations for policymakers to consider interventions that can mitigate the negative impact of food price fluctuations